LA-ICPMS ANALYSES OF SILICATE MELT INCLUSIONS IN CO-PRECIPITATED MINERALS: QUANTIFICATION, DATA ANALYSIS AND MINERAL/MELT PARTITIONING - Zajacz Z.; Halter W. (My University, 2007)
We present a new approach to determine the composition of silicate melt inclusions (SMI) using LA-ICPMS. In this study, we take advantage of the occurrence of SMI in co-precipitated mineral phases to quantify their composition without depending on additional sources of information. Quantitative SMI analyses are obtained by assuming that the ratio of selected elements in SMI trapped in different phases are identical. In addition Fe/Mg exchange equilibrium between olivine and melt was successfully used to quantify LA-ICPMS analyses of SMI in olivine. Results show that compositions of SMI from the different host minerals are identical within their uncertainty. Thus (1) the quantification approach is valid; (2) analyses are not affected by the composition of the host phase; (3) the derived melt compositions are representative of the original melt, excluding significant syn- or postentrapment modification such as boundary layer effects or diffusive reequilibration with the host mineral. With this data we established a large dataset of mineral/melt partition coefficients for the investigated mineral phases in hydrous calc-alkaline basaltic-andesitic melts. The clinopyroxene/melt and plagioclase/melt partition coefficients are consistent with the lattice strain model of Blundy and Wood [Blundy, J., Wood B., 1994. Prediction of crystal-melt partition-coefficients from elastic-moduli. Nature 372, 452-454]. © 2006 Elsevier Inc. All rights reserved.